2003
DOI: 10.1159/000074046
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Severity of Symptoms of Asthma, Allergic Rhinoconjunctivitis, and Atopic Eczema in 6- to 7-Year-Old Nigerian Primary School Children: The International Study of Asthma and Allergies in Childhood

Abstract: Objective: To determine the prevalence and severity of symptoms of asthma, allergic rhinoconjunctivitis and eczema in Nigerian children aged 6–7 years. Subjects and Methods: A cross-sectional study of selected children in primary schools in Ibadan, Nigeria was conducted using phase I of the International Study of Asthma and Allergies in Childhood (ISAAC) format. Standardized questionnaires were distributed to parents and guardians of 2,325 children aged 6–7 years in 31 primary schools randomly selected among 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 14 publications
4
36
1
2
Order By: Relevance
“…5 Abdurrahman et al 10 and Onazi et al 14 . However, the finding in both ISAAC studies done by Faladeet al 20,21 which reported eczema as a common disorder (10.1% in 6-7year old and 26.1% in 13-14year old respectively) was not in agreement with this study as only 2.9% of asthmatic subjects had atopic dermatitis. This may be due to the difference in sample size where 1,704 6-7year olds and 3,058 13-14 year olds were studied by Faladeet al 20,21 respectively.…”
Section: Discussioncontrasting
confidence: 87%
“…5 Abdurrahman et al 10 and Onazi et al 14 . However, the finding in both ISAAC studies done by Faladeet al 20,21 which reported eczema as a common disorder (10.1% in 6-7year old and 26.1% in 13-14year old respectively) was not in agreement with this study as only 2.9% of asthmatic subjects had atopic dermatitis. This may be due to the difference in sample size where 1,704 6-7year olds and 3,058 13-14 year olds were studied by Faladeet al 20,21 respectively.…”
Section: Discussioncontrasting
confidence: 87%
“…The prevalence of 9.58% self-reported in this study is consistent 10.7% and 10.2% reported in previous studies on diabetes prevalence [51,52].…”
Section: Discussionsupporting
confidence: 91%
“…More recently, asthma, COPD, chronic cough and/or rhinitis induced by occupational exposure have been identified in developing countries (591,(624)(625)(626)(627)(628)(629)(630)(631)(632)(633)(634)(635)(636)(637)(638).…”
Section: Other Mitesmentioning
confidence: 99%